2006
DOI: 10.1051/fruits:2006023
|View full text |Cite
|
Sign up to set email alerts
|

Mise en évidence d’une androdioécie morphologique et d’une « hétérostigmatie » chezSclerocarya birrea(A. Rich.) Hochst

Abstract: Article original Description of a morphological androdioecy and of a "heterostigmaty" for Sclerocarya birrea (A. Rich.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…caffra) in southern and central Africa has largely been reported in the literature as dioecious. However, the female flowers also bear staminodes which have been proved to have viable pollen and suggest that the species is morphologically androdioecious (Diallo et al 2006). Yet, no selfing experience was carried out to verify whether these supposed hermaphrodites flowers were self-compatible, or pollinated other plants in nature.…”
Section: Sex Ratiomentioning
confidence: 96%
See 2 more Smart Citations
“…caffra) in southern and central Africa has largely been reported in the literature as dioecious. However, the female flowers also bear staminodes which have been proved to have viable pollen and suggest that the species is morphologically androdioecious (Diallo et al 2006). Yet, no selfing experience was carried out to verify whether these supposed hermaphrodites flowers were self-compatible, or pollinated other plants in nature.…”
Section: Sex Ratiomentioning
confidence: 96%
“…However, Diallo et al (2006) have found the Sahel populations in Senegal to be morphologically androdioecious, and Hall (2002) have reported the presence of occasional female flowers in the most proximal inflorescences of the shoots on predominantly male trees. Diallo et al (2006) found that pollens of Sclerocarya birrea ''hermaphrodites'' were viable, but they did not carry out any selfing experience. Androdioecy is a rare sexual system in plants and animals in which males cooccur with cosexuals (Charlesworth 1984;Pannell 2002).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Celles-ci sont établies sur la distance entre les arbres-mères, leur état sanitaire et la taille de l'échantillon. Compte tenu du caractère androdioïque de l'espèce (Diallo et al, 2006), 20 arbres visuellement sains, distants l'un de l'autre d'environ 100 m, ont été échantil-lonnés au sein de chaque population ; 40 fruits arrivés à maturité commerciale ont été récoltés sur chaque arbre.…”
Section: Récolte Des Fruitsunclassified
“…However, studies to date, have focused on genetic diversity (Bationo-Kando et al, 2012), morphology (Bationo-Kando et al, 2008), anatomy (Sérémé, 1996;Diallo et al, 2006), or on the physicochemical composition of S. birrea the fruit (Bationo-Kando et al, 2009). On the other hand, data on the production and exploitation of the plant, by rural and urban populations, are still basic or non-existent.…”
Section: Introductionmentioning
confidence: 99%